2017
DOI: 10.1007/s10948-016-3963-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical Temperature of Smart Meta-superconducting MgB2

Abstract: Enhancing the critical temperature (TC) is important not only to the practical applications but also to the theories of superconductivity. MgB2 is a type II superconductor with a TC of 39 K, which is very close to the McMillan limit. Improving the TC of MgB2 is challenging but significant. Inspired by the metamaterial structure, we designed a smart meta-superconductor that consists of MgB2 microparticles and Y2O3:Eu 3+ nanorods. In the local electric field, Y2O3:Eu 3+ nanorods will generate electroluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Figure 3 shows the normalized R–T curves of MgB 2 doped with m-Y 2 O 3 :Eu 3+ /Ag with different Ag contents. On the basis of the results of our previous study 45,46 , the content of m-Y 2 O 3 :Eu 3+ /Ag in the four samples was fixed at 2.0 wt.%. The Ag contents of m-Y 2 O 3 :Eu 3+ /Ag in the four samples were 1.0%, 4.0%, 5.0%, and 8.0%, as shown in the figure, and their T C values were 34.8–35.6, 36.0–36.8, 37.2–38.0, and 34.8–35.6 K, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows the normalized R–T curves of MgB 2 doped with m-Y 2 O 3 :Eu 3+ /Ag with different Ag contents. On the basis of the results of our previous study 45,46 , the content of m-Y 2 O 3 :Eu 3+ /Ag in the four samples was fixed at 2.0 wt.%. The Ag contents of m-Y 2 O 3 :Eu 3+ /Ag in the four samples were 1.0%, 4.0%, 5.0%, and 8.0%, as shown in the figure, and their T C values were 34.8–35.6, 36.0–36.8, 37.2–38.0, and 34.8–35.6 K, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a dopant, m-Y 2 O 3 :Eu 3+ /Ag exerts an impurity effect that decreases T C . Meanwhile, as an EL material, m-Y 2 O 3 :Eu 3+ /Ag exerts an EL exciting effect that increases T C 45,46 . An obvious competitive relationship exists between the impurity effect and the EL exciting effect.…”
Section: Resultsmentioning
confidence: 99%
“…3a nanosheets increases by 1.2 K compared with that of pure MgB2, which may be due to the Y2O3:Eu 3+ nanosheets EL material distributed around the MgB2 particles to form a special response meta-structure. Y2O3:Eu 3+ nanosheets would generate an EL during the measurement of R-T curve of the sample, which may improve the superconducting transition temperature [19]. (4) The Fig.…”
Section: Preparation Of Doped Mgb2-based Superconductorsmentioning
confidence: 99%
“…When evaluating the curve of the temperature dependence of resistivity (R-T) of the samples, in the local electric field, MgB2 particles act as microelectrodes, which promote the EL of inhomogeneous phase EL materials, and found inhomogeneous phase significantly improves the TC [18,19]. In this paper, the responses of the critical temperature of MgB2 to inhomogeneous phase doping and changing the applied electric field are systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the doping of Y 2 O 3 :Eu 3+ EL materials increases the T C of MgB 2 . We believe that the Y 2 O 3 :Eu 3+ materials generate an EL under the action of an external electric field and that EL energy injection promotes the formation of Cooper pairs; the T C of MgB 2 is improved via EL [ 35 , 36 , 37 , 38 , 39 ]. At the same time, a smart meta-superconductor B(P)SCCO consists of the B(P)SCCO matrix and an inhomogeneous phase Y 2 O 3 :Eu 3+ or Y 2 O 3 :Eu 3+ +Ag was constructed in BSCCO superconductors.…”
Section: Introductionmentioning
confidence: 99%